Binding of ligands containing carbonyl and phenol groups to iron(iii): new Fe6, Fe10 and Fe12 coordination clusters. Issue 10 (22nd February 2017) - Kitos, Alexandros A.; Papatriantafyllopoulou, Constantina; Tasiopoulos, Anastasios J.; Perlepes, Spyros P.; Escuer, Albert; Nastopoulos, Vassilios
Abstract : A series of polynuclear Fe III clusters with unique or rare topologies and interesting magnetic properties have been obtained from the reactions of iron(ii )/(iii ) sources and hydroxyphenone ligands. Abstract : The initial use of ligands 2′-hydroxyacetophenone (HL 1 ), 2-hydroxybenzophenone (HL 2 ) and 2, 2′-dihydroxybenzophenone (H2 L 3 ) in iron(iii ) chemistry is described. The syntheses and crystal structures are reported for five iron(iii ) clusters: [Fe10 O4 (OMe)14 (L 1 )6 (MeOH)2 ](NO3 )2 ·3MeOH (1 ·3MeOH), [Fe12 O4 (OH)(OMe)17 (L 1 )8 ](ClO4 )2 ·2H2 O (2 ·2H2 O), [Fe10 O4 (OMe)14 Cl4 (L 2 )4 (MeOH)2 ] (3 ), [Fe10 O4 (OMe)14 (L 2 )6 (py)2 ](ClO4 )2 ·MeOH (4 ·MeOH), where py = pyridine, and [Fe6 O2 (OEt)6 (O2 CMe)2 (L 3 )2 (HL 3 )2 ] (5 ). The molecular structures of the decanuclear clusters1, 3 and4 are organized around a {Fe10 (μ4 -O)4 (μ3 -OMe)2 (μ-OMe)12 } 8+ core consisting of ten Fe3 O4 face-sharing defective cubane units. The core of2 consists of a {Fe12 (μ4 -O)4 (μ3 -OMe)4 (μ-OH)(μ-OMe)13 } 10+ unit composed of twelve Fe3 O4 face-sharing defective cubanes. The ligands (L 1 ) − and (L 2 ) − in1–4 adopt the O, O ′-bidentate chelating coordination mode and their roles are to terminate the further aggregation of the Fe III /O 2− /RO − cores. Complex5 contains the {Fe6 (μ4 -O)2 (μ-OEt)6 (μ-Ocarbonyl )2 } 4+ core, where the μ-Ocarbonyl atoms are the bridging carbonyl oxygens of the two η 1 :η 2 :η 1 :μ (L 3 ) 2− ligands; the (HL 3 ) − groups behave as Ophenolate, Ocarbonyl -bidentate chelating ligands with the neutral hydroxyl group being unbound to the Fe III atoms. The core is composed of four Fe3 O4 face-sharing defective cubanes. The Fe III atoms in1–5 are all six-coordinate with distorted octahedral geometries. The IR spectra of the complexes are discussed in terms of the known coordination modes of the ligands and the ionic character of nitrates and perchlorates. Variable-temperature magnetic susceptibility and variable-field magnetization measurements establish that2, 3 and5 have S = 3, 0 and 5 ground states, respectively. The susceptibility data for5 were fitted using a 3- J model indicating the simultaneous presence of both antiferromagnetic and ferromagnetic Fe III ⋯Fe III exchange interactions. Known magnetostructural correlations in oxido-bridged iron(iii ) systems have been applied to rationalise the magnetic behaviour of the three clusters. The results of the present study demonstrate the utility of HL 1, HL 2 and H2 L 3 in the stabilisation of robust iron(iii )/oxido/alkoxido clusters.